Two new species of the cicada genus Auritibicen (Hemiptera: Cicadidae) from China - Wang, Jiali; Lu, Zhuorui; Yang, Jingyuan; Wei, Cong (Zootaxa, 2026)
Two new species of the genus Auritibicen, A. nani Wang & Wei sp. nov. and A. bofani Wang & Wei sp. nov., are described, which were discovered from Mount Emei and the Shennongjia Mountains, China, respectively. The relationships of the two new species to related taxa are discussed based on morphological characters and a molecular phylogeny of Auritibicen reconstructed using sequences of the barcoding gene (COI).